2008
DOI: 10.1038/oby.2008.397
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship of ENPP1/PC‐1 Variants to Obesity in a Turkish Population

Abstract: The ectoenzyme ENPP1 (also termed membrane glycoprotein PC-1 or ENPP1/PC-1) is an inhibitor of insulin-induced activation of the insulin receptor. There is evidence from previous studies that coding variants of ENPP1/PC-1 (K121Q) are associated with type 2 diabetes (T2D) and obesity. Studies in the general Turkish population have demonstrated: unique plasma lipid characteristics; a high prevalence of cardiovascular risk factors; and an increased prevalence of obesity and T2D. We investigated, therefore, the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…A noteworthy confounder is that ENPP1 variants differentially modulate insulin receptor signaling 157 and K173Q and other SNPs in ENPP1 may have an indirect effect on parameters affecting arterial calcification in certain populations.…”
Section: B Specific Methods To Identify Genetic Factors Contributingmentioning
confidence: 99%
“…A noteworthy confounder is that ENPP1 variants differentially modulate insulin receptor signaling 157 and K173Q and other SNPs in ENPP1 may have an indirect effect on parameters affecting arterial calcification in certain populations.…”
Section: B Specific Methods To Identify Genetic Factors Contributingmentioning
confidence: 99%
“…Similar data have been reported for TCF7L2, which is 84 insulin resistance prospectively predicts decreased BMI. 85 Accordingly, several genetic variants that predict increased insulin sensitivity are associated with increased BMI, whereas genetic variants that are associated with insulin resistance are also associated with reduced BMI. 4 In vitro studies suggest a direct effect of the Q121 variant of ENPP1 on adipogenesis.…”
Section: Reviewsmentioning
confidence: 99%
“…We found that both the Q121 variant and the "at risk" haplotype were associated with obesity in males but not in females. 30 Wan et al reported a gender difference in the association between the Q121 variant and the risk of obesity in a Chinese population. 29 In contrast to our previous study, 30 they found that female subjects with the Q allele were at higher risk for obesity than males.…”
Section: Enpp1/pc-1 Haplotype Analysis In the Study Populationmentioning
confidence: 99%
“…30 Wan et al reported a gender difference in the association between the Q121 variant and the risk of obesity in a Chinese population. 29 In contrast to our previous study, 30 they found that female subjects with the Q allele were at higher risk for obesity than males. We did not fi nd any gender-SNP(s) interaction on TG levels in the present study.…”
Section: Enpp1/pc-1 Haplotype Analysis In the Study Populationmentioning
confidence: 99%